Pilot-scale study of methane-assisted catalytic bitumen partial upgrading - Zhaofei Li; Ali Omidkar; Hua Song (Fuel Processing Technology)
The direct utilization of heavy and extra-heavy crude oils presents a formidable challenge due to their inherent physical and chemical properties such as high C/H ratio, extremely high viscosity and density, low APIo, super low mobility, high asphaltene and impurity (Fe, Ni, Co, S, N, etc.) contents. To tackle these problems cost-effectively, we have proposed and established a novel technique, distinct from conventional hydrotreating, for catalytic partial upgrading of extra heavy crudes with co-fed methane and a multi-functional catalyst. This technique has been further optimized using lab-scale batch reactors (100 mL, 300 mL), bench-scale and pilot-scale fixed bed reactors with their processing capacity of 250 mL/day and 20 L/day, respectively. The feasibility, stability, and profitability of this technique have been successfully verified using all these facilities and a wide variety of feedstock. Yet, further scale-up is necessary to advance this technique towards commercialization in industry. In this study, a pilot-scale prototype unit (processing capacity of 1 barrel/day) was designed and manufactured based upon the previous achievements, and a bitumen sample recovered from the Steam Assisted Gravity Drainage (SAGD) process was chosen as a typical extra heavy crude for the upgrading. A 30-day upgrading has been conducted smoothly without clogging and a liquid yield of 96.7 % was observed with remarkable enhancements in product quality. The notable decreases in density, viscosity, TAN, asphaltene content, and sulfur content were confirmed and consistent with previous results. A low olefin content implies excellent stability and compatibility of the liquid product. Additionally, a preliminary TEA (Techno-Economic Assessment) and LCA (Life-Cycle Analysis) have been conducted and the beneficial features of this novel technique have been confirmed with higher profitability, lower cost, and lower carbon footprint. This study further consolidates the advantages of this promising technique as a cost-effective and environmentally friendly alternative to hydrotreating for processing extra heavy crudes.